The Rise of Environmental, Social, and Governance (ESG): Assessing the Impact and Implications for Global Business Practices and Policy Formulation - Warouw, Felly Ferol; Mashudi; Arafah, Mudrikatul; Noviany, Henny; Hendarto, Totok (International Journal of Science and Society, 2024)
Increased awareness of environmental, social, and governance (ESG) issues has brought about significant changes in global business practices. Companies now face pressure to integrate ESG aspects into their strategies and operations, in line with the demands of consumers, investors, and regulators. In this context, the role of ESG in shaping public policy and market dynamics is becoming increasingly important, influencing investment decisions and business continuity. This research aims to assess the impact and application of ESG on global business practices and policy formulation. This research uses a qualitative approach, with data obtained from the results of previous research and related studies, and content analysis was carried out to process the data. The results of this research show that integrating ESG into business strategy is not just ethical, but is also critical to achieving long-term success. The impact of ESG on consumer preferences and markets has driven companies to innovate and adapt their operations. ESG-related public policies and regulations encourage collaboration between sectors and influence cross-border business operations. In the investment context, ESG has become an important factor in portfolio management and financing decisions. Overall, ESG has become an important catalyst in shaping the future of sustainable and responsible business.